lmmunomodulatory Effect of Andrographis panicu/ata during Lead Induced Toxicity in Broilers - Chandewar, A. S.; Ingole, R. S.; Joshi, M. V.; Hedau, Madhuri; Hajare, S. W.; lngawale, M. V. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
The effect of dietary lead exposure on immunomodulation of broilers and possible ameliorative effect of Andrographis paniculata were studied. One hundred broiler chicks were randomly divided into five equal groups of 20 each. Group TO served as control while group T1, T2, T3 and T4 birds were provided commercial diet with lead acetate at the dose of 300 ppm in feed. Powder of dry leaves of Andrographis paniculata was mixed in the feed of group T2, T3 and T 4 chicks at the dose of 2 gm, 3 gm and 4 gm/kg of feed respectively and fed for 4 weeks. Significant decrease in HI titres in T1 group and significant increase in T4 group suggested increased haemagglutination titre (HI) response. The maximum skin thickness and diameter on 24th and 48th hours was observed in control group birds (TO) and was comparable with T4 group. Microscopically spleen, thymus and bursa of fabricius revealed increase in lymphoid population in birds fed lead acetate along with Andrographis paniculata compared to T1 group. We concluded that Andrographis paniculata has immunomodulatory effect during lead toxicity in broilers.